ZerowasteX - Ked Eryaddy, Nor Shahila; Shamsuri, Mohammad Ridwan; Nor Azman, Muhammad Afiq; Ahmad Nazir, Siti Nuralia (2025)
ZerowasteX Sdn. Bhd. is an innovative Kluang-based partnership that develops and markets solar-powered compost bins designed to efficiently convert organic waste into nutrient-rich compost. Targeting schools, universities, local councils, and eco-conscious households, the company emphasizes user-friendly features such as automatic grinding, compact design, and sustainability. Its strategy focuses on digital marketing, community engagement, and educational outreach, supported by strong administrative, operational, and financial planning. With projected sales growth, a commitment to legal compliance and quality, and a vision aligned with global sustainability goals, ZerowasteX aims to become a leading force in Malaysia’s green technology and circular economy.